Applications to statutory donor registers in Victoria, Australia: information sought and expectations of contact. (December 2019) - Dempsey, Deborah; Kelly, Fiona; Horsfall, Briony; Hammarberg, Karin; Bourne, Kate; Johnson, Louise
Abstract: Knowledge of genetic origins is widely believed to have consequences for health, family belonging and personal identity. Donor linking is the process by which donors, recipient parents (RP) and donor-conceived people (DCP) gain access to identifying information about each other. This paper reports on the information and contact sought by donor-linking applicants to the central and voluntary registers in the state of Victoria, Australia, which has one of the most comprehensive donor-linking legislative frameworks in the world. Applicants to the Victorian registers complete a statement of reasons (SOR), a written document that is given to the subject of the application, outlining their reasons for applying and their short- and long-term goals. SOR written by applicants between 29 June 2015 and 28 February 2017 who had agreed to be recontacted for research were analysed. Forty-two of 93 eligible applicants took part (45%). All applications pertained to donor sperm. RP were the largest applicant group ( n  = 19) followed by DCP ( n  = 17) and donors ( n  = 6). All applicants wanted personal information and most expressed a desire for contact. Single mothers of young children used the registers more than any other parent group, indicating that family structure may influence application patterns. While it is apparent that all applicants are eager for information and some form of interpersonal contact, further research is needed on how the legal and policy landscape of different jurisdictions influences expectations, as well as what happens after parties are linked.